Grease lubrication in rolling bearings - Lugt, Piet M. (Tribology in practice series., 2013)
"The definitive book on the science of grease lubrication for roller and needle bearings in industrial and vehicle engineering.Grease Lubrication in Rolling Bearings provides an overview of the existing knowledge on the various aspects of grease lubrication (including lubrication systems) and the state of the art models that exist today. The book reviews the physical and chemical aspects of grease lubrication, primarily directed towards lubrication of rolling bearings.The first part of the book covers grease composition, properties and rheology, including thermal and dynamics properties. Later chapters cover the dynamics of greased bearings, including grease life, bearing life, reliability and testing. The final chapter covers lubrications systems - the systems that deliver grease to the components requiring lubrication.Grease Lubrication in Rolling Bearings: Describes the underlying physical and chemical properties of grease. Discusses the effect of load, speed, temperature, bearing geometry, bearing materials and grease type on bearing wear. Covers both bearing and grease performance, including thermo-mechanical ageing and testing methodologies. It is intended for researchers and engineers in the petro-chemical and bearing industry, industries related to this (e.g. wind turbine industry, automotive industry) and for application engineers. It will also be of interest for teaching in post-graduate courses"--Provided by publisher.